Charge characteristics in relation to mineralogy of selected soils from South-east Asia - Jusop, Shamsuddin; Salleh, Ruziah; Mohd Hanif, Ahmad Husni; Awang, Kamis (Universiti Putra Malaysia Press, 1996)
The mineralogy and charge characteristics of 7 soils from the Philippines, Indonesia and Malaysia were studied. The soils consisted of an Entisol, 3 Alfisols, an Andisol and 2 Oxisols. Smectite, mica and quartz were present in the clay fraction of the Entisol. In the Alfisols, smectite and kaolinite were the dominant minerals. The Andisol was dominated by halloysite, whereas the Oxisols were dominated by kaolinite and oxides. The amount of kaolinite increased towards the surface, while halloysite decreased, indicating the transformation of halloysite to kaolinite during the course of weathering. Differences in mineralogy of the various soil types were reflected clearly in the differences in charge characteristics. Soils with smectite (Entisol and Alfisol) had high a negative charge. The Andisol, which contained halloysite, and the Oxisol, with kaolinite and oxides, had high amounts ofpositive charge, but moderate amounts ofnegative charge. The availability ofCa in the soils depended upon exchangeable Ca and the efJective cation exchange capacity (ECEC).